Cloud services as the ultimate gate(keeper). (28th June 2019) - Lundqvist, Björn
Abstract: In the Internet of Things (IoT), the amount and smart use of data will determine whether or not a firm can compete successfully. Manufacturing firms will collect data through sensors in their devices and, at least in the cases of SMEs, likely store the collected data in the cloud, purchasing cloud services and storage from the large e-platform providers doubling as cloud providers. The e-platform providers will also collect data from users of their other services. These data are often generated by the same firms that purchase cloud services when they use the e-platforms to sell goods and services. Access to the data and to data analytics on fair business terms, and the possibility to switch cloud and service providers are vital for the SMEs and, in general, to create a competitive and vibrant IoT. However, cloud and e-platform customers seem to be facing difficulties. According to the EU Commission, SMEs are finding it particularly hard to engage cloud and e-platform providers, and to gain access to cloud services on reasonable, transparent terms. The contracts are skewed in favour of the cloud providers. The customers get locked in and may be obliged to agree not to assert any of their intellectual property rights vis-à-vis the cloud provider or the cloud provider's network. Moreover, the cloud and e-platform providers may under certain circumstances access and make use of the users' data, and that may give them a competitive advantage vis-à-vis the users, since the providers may have access to much more data, even data originating from the users' competitors, suppliers, customers, etc. They can thus use all the data available to them to obtain a fuller picture of whole industries, and they may use that advantage in data to leverage and enter users' markets. Indeed, they may use the data in the cloud for data-driven business strategies to enter the core market of the firms that have provided them with data in the first place. This article discusses whether competition law can address the conduct of the cloud and e-platform providers, so that firms may access and make use of all the possibilities that the IoT harbours.